Project Based Learning (PjBL) Berbasis Etnosains Untuk Meningkatkan Ketrampilan Berpikir Kritis Mahasiswa : Tinjauan Pustaka - Ilham Kamaruddin; Delia Subrayanti; Rasimin Rasimin; Triyanto Triyanto; MS Viktor Purhanudin; Ns.Novita Amri (Departement of Mathematics Education, 2024)
This study aims to explore the concept of ethnoscience-based Project Based Learning (PjBL) in improving students' critical thinking skills. A literature review was conducted to understand the concepts of PjBL, ethnoscience, and their relationship with the development of critical thinking skills. PjBL is a learning approach that provides in-depth learning experiences through real projects, while ethnoscience integrates local knowledge in the learning process. These two concepts, when combined, can create a learning environment that is relevant to students' cultural and environmental contexts. This literature review reveals that ethnoscience-based PjBL can enhance students' critical thinking skills through engagement in projects relevant to the local community. Collaboration with local communities also broadens students' understanding of social and cultural issues. The results of this literature review highlight the importance of implementing ethnoscience-based PjBL in higher education to prepare students to become individuals who are able to think critically, analytically, and creatively in facing complex challenges in society.